2009
DOI: 10.1073/pnas.0902169106
|View full text |Cite
|
Sign up to set email alerts
|

Predicting weakly stable regions, oligomerization state, and protein–protein interfaces in transmembrane domains of outer membrane proteins

Abstract: Although the structures of many ␤-barrel membrane proteins are available, our knowledge of the principles that govern their energetics and oligomerization states is incomplete. Here we describe a computational method to study the transmembrane (TM) domains of ␤-barrel membrane proteins. Our method is based on a physical interaction model, a simplified conformational space for efficient enumeration, and an empirical potential function from a detailed combinatorial analysis. Using this method, we can identify we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(114 citation statements)
references
References 45 publications
4
109
0
Order By: Relevance
“…Thus, our results imply that dynamics in the N-terminal region are relevant for hexokinase binding. This interpretation is in line with recent findings showing destabilized regions of outer membrane proteins to be preferentially involved in proteinprotein interaction (46).…”
Section: μS-ms Dynamics Are Significantly Increased For the N-terminasupporting
confidence: 82%
“…Thus, our results imply that dynamics in the N-terminal region are relevant for hexokinase binding. This interpretation is in line with recent findings showing destabilized regions of outer membrane proteins to be preferentially involved in proteinprotein interaction (46).…”
Section: μS-ms Dynamics Are Significantly Increased For the N-terminasupporting
confidence: 82%
“…The residues that required relatively high empirical energy to insert into the lipid bilayer were termed as weakly stable residues. The empirical energy function (TmSIP) used is derived from bioinformatics analysis of ␤-barrel membrane proteins (32)(33)(34). Those strands with energy higher than the mean energy of all of the strands were regarded as weakly stable.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that these weakly stable regions strongly indicate the existence of protein-protein interaction sites. Using 25 ␤-barrel membrane proteins, the oligomeric state of each protein was predicted correctly, and the protein-protein interaction interfaces were recovered at an accuracy of 78% (32).…”
Section: Structure-and Computation-based Selection Of Predicated Vdacmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown how lowaffinity cadherin dimers formed through β-strand swapping can mediate and control highly specific intercellular adhesion (10,27). In another study it was proposed that β-barrel membrane proteins can oligomerize through the weakly stable interfacial beta-strands (28), while the C-terminal helix in certain p53 proteins might be essential for stabilizing tetramers (29). Finally, the manual inspection of insertions and deletions of homologous proteins in different oligomeric states revealed that for about a quarter of them certain protein regions are responsible for enabling or disabling the oligomeric interfaces (30).…”
mentioning
confidence: 99%